GERAKAN MADRASAH INOVATIF DALAM MENINGKATKAN KEPRIBADIAN SISWA DI MADRASAH IBTIDAIYAH NEGERI 3 JOMBANG: IMPLEMENTASI GERAKAN MADRASAH INOVATIF DALAM MENINGKATKAN KEPRIBADIAN SISWA - anas al abror anas; Rofiatul Hosna (Prodi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Daruttaqwa Gresik, 2022)
Innovation is a change from something new to another or different from the previous one, which is done intentionally and planned (not by chance). There are so many problems faced by Islamic educational institutions (madrasas), especially at MIN 3 Jombang, the quality of the student's personality is still far from perfect, although there are some parts to be proud of. This can not be separated from many factors involving a number of components that require changes towards improvement. Madrasah Ibtidaiyah are elementary-level madrasas that require change or innovation, reorganizing the system in education. with the holding of this innovation madrasa movement, at MIN 3 Jombang it will improve the personality of students who are good and superior. Researchers are interested in knowing how far this Madrasa Innovation Movement can improve students' personality. Thus, this research was conducted to find out how the education system at MIN 3 Jombang is and to find out how the implementation of the Madrasa Innovation Movement program is to improve students' personalities. In this study using descriptive qualitative research, and in collecting data the authors used data reduction, data display, conclusion drawing and verification, as well as in testing the validity of the data with credibility. The results of this study stated that at MIN 3 Pucangsimo Jombang there was a significant increase as indicated by students' awareness of environmental cleanliness, polite attitude towards teachers, diligent worship, and always maintaining or covering genitalia,